Responses of Community Leaders and Non-leaders to the Land Use Act (1978) in Oyo State of Nigeria - Jibowo, A. A. (Faculty of Agriculture, University of Ife, 2015)
This study determined the knowledge of some specific provisions of the Land Use Act by the respondents, their reactions to the Act, the personal, social and economic characteristics and the relationships of these to their attitudes towards the Act. Interviews were carried out among 110 leaders and 170 non-leaders between December 1978 and February 1979. Leaders were generally older, earned higher incomes than non-leaders; majority of leaders were full-time farmers. The respondents did not claim much landed properties. Most respondents were ignorant of many specific provisions of the Act and did not apply for land allocation. The majority expressed an unfavourable attitude towards the Act. Formal education, borrowing of farmland, receiving compensations on land, age, length of community residence and years of schooling were associated with attitude among the respondents. Occupation, method of acquiring houseland, and some other characteristics were associated with attitude among leaders. Community identification, place of origin, and some other characteristics were associated with attitude among nonleaders. Understanding these relationships should facilitate the design and implementation of public measures to promote the implementation of the Act.